Orthopaedic Surgery Residents and Program Directors Agree on How Time Is Currently Spent in Training and Targets for Improvement. Issue 4 (April 2016) - Camp, Christopher L.; Martin, John R.; Karam, Matthew D.; Ryssman, Daniel B.; Turner, Norman S.
Abstract: Background: Although much attention has been paid to the role of deliberate practice as a means of achieving expert levels of performance in other medical specialties, little has been published regarding its role in maximizing orthopaedic surgery resident potential. As an initial step in this process, this study seeks to determine how residents and program directors (PDs) feel current time spent in training is allocated compared with a theoretical ideal distribution of time. Questions/purposes: According to residents and PDs, (1) how do resident responsibilities change by level of training as perceived and idealized by residents and PDs? (2) How do resident and PD perceptions of current and ideal time distributions compare with one another? (3) Do the current training structures described by residents and PDs differ from what they feel represents an ideal time allocation construct that maximizes the educational value of residency training? Methods: A survey was sent to orthopaedic surgery resident and PD members of the Midwest Orthopedic Surgical Skills Consortium asking how they felt residents' time spent in training was distributed across 10 domains and four operating room (OR) roles and what they felt would be an ideal distribution of that time. Responses were compared between residents and PDs and between current schedules and ideal schedules. Results: Both residents and PDs agreed that time currently spent in training differs by postgraduate year with senior‐level residents spending more time in the OR (33.7% ± 8.3% versus 17.9% ± 6.2% [interns] and 27.4% ± 10.2% [juniors] according to residents, p < 0.001; and 38.6% ± 8.1% versus 11.8% ± 6.4% [interns] and 26.1% ± 5.7% [juniors] according to PD, p < 0.001). The same holds true for their theoretical ideals. Residents and PDs agree on current resident time allocation across the 10 domains; however, they disagree on multiple components of the ideal program with residents desiring more time spent in the OR than what PDs prefer (residents 40.3% ± 10.3% versus PD 32.6% ± 14.6% [mean difference MD, 7.7; 95% confidence interval CI, 4.4, 11.0], p < 0.001). Residents would also prefer to have more time spent deliberately practicing surgical skills outside of the OR (current 1.8% ± 2.1% versus ideal 3.7% ± 3.2% [MD, −1.9; 95% CI, −.2.4 to −1.4], p < 0.001). Both residents and PDs want residents to spend less time completing paperwork (current 4.4% ± 4.1% versus ideal 0.8% ± 1.6% [MD, 3.6; 95% CI, 3.0‐4.2], p < 0.001 for residents; and current 3.6% ± 4.1% versus ideal 1.5% ± 1.9% [MD, 2.1; 95% CI, 0.9‐3.3], p < 0.001 for PDs). Conclusions: Residents and PDs seem to agree on how time is currently spent in residency training. Some differences of opinions continue to exist regarding how an ideal program should be structured; however, this work identifies a few potential targets for improvement that are agreed on by both residents and PDs. These areas include increasing OR time, finding opportunities for deliberate practice of surgical skills outside of the OR, and decreased clerical burden. This study may serve as a template to allow programs to continue to refine their educational models in an effort to achieve curricula that meet the desired goals of both learners and educators. Additionally, it is an initial step toward more objective identification of the optimal educational structure of an orthopaedic residency program.